14.4: Diffraction Simulation of Camera Under Display. (24th February 2021) - Zhang, Zhenhua
Abstract : This paper provided a method to simulate diffraction of Camera Under Display (CUD). To balance the display performance of CUD area and front camera image quality, special panel lamination was designed to meet the requirement. Due to the micro level size of pixel texture, strong optical diffraction effect was caused and image on CMOS was blurred. This paper built a way to simulate the Modulation Transfer Function of different pixel patterns display and promote promising research direction for camera under display.